Long-term efavirenz autoinduction and its effect on plasma exposure in HIV patients - Ngaimisi, Eliford; Mugusi, S; Minzi, O M; Sasi, P; Riedel, Klaus-Dieter; Suda, A; Ueda, N; Janabi, M; Mugusi, F; Haefeli, Walter E.; Burhenne, J; Aklillu, E (Clinical pharmacology & therapeutics, 2010)
We investigated the influence of gender and pharmacogenetic variations on long-term efavirenz autoinduction and disposition among patients with HIV in Tanzania (N = 129). Plasma concentrations (at 16 h) of efavirenz and 8-hydroxyefavirenz were quantified at weeks 4 and 16 of therapy. Genotyping was performed to identify cytochrome P450 (CYP) 2B6*6, CYP3A5*3, *6, and *7, and ABCB1-3435 C/T genotypes. There were reductions in the median efavirenz concentration (Wilcoxon matched-pair test P < 0.001) and efavirenz/8-hydroxyefavirenz ratio (P < 0.001) by 19 and 32%, respectively, at week 16 as compared with week 4. The proportion of patients with efavirenz concentration <1 µg/ml at week 16 was higher by 67, 25, and 5% in CYP2B6*1/*1, *1/*6, and *6/*6 genotypes, respectively. The defined therapeutic range based on observed plasma concentrations is affected by the time point of sampling and the CYP2B6 genotype. The effect of efavirenz autoinduction on reducing plasma exposure continues up to week 16 and predominantly affects CYP2B6 extensive metabolizers. Among CYP2B6 slow metabolizers, the presence of a CYP3A5 genotype allele is associated with greater effects of efavirenz autoinduction on plasma concentrations of the drug. The cumulative induction may influence the long-term antiretroviral therapy outcome, particularly in CYP2B6*1 carriers. Clinical Pharmacology & Therapeutics (2010) 88 5, 676-684. doi: 10.1038/clpt.2010.172
Gesehen am 12.05.2023